Examining the Interplay of Processes Across Multiple Time-Scales: Illustration With the Intraindividual Study of Affect, Health, and Interpersonal Behavior (iSAHIB) - Ram, N.; Conroy, D.; Pincus, A.; Lorek, A.; Rebar, Amanda; Roche, M.; Coccia, M.; Morack, J.; Feldman, J.; Gerstorf, D. (2014)
Human development is characterized by the complex interplay of processes that manifest at multiple levels of analysis and time-scales. The authors introduce the Intraindividual Study of Affect, Health and Interpersonal Behavior as a model for how multiple time-scale study designs facilitate more precise articulation of developmental theory. Combining age heterogeneity, longitudinal panel, daily diary, and experience sampling protocols, the study made use of smartphone and web-based technologies to obtain intensive longitudinal data from 150 persons age 18 to 89 years as they completed three 21-day measurement bursts, spanning 8,557 days and 64,112 social interactions, as they went about their daily lives. The authors illustrate how multiple time-scales of data can be used to articulate bioecological models of development and the interplay among more "distal" processes that manifest at "slower" time-scales (age-related differences and burst-to-burst changes in mental health) and more "proximal" processes that manifest at "faster" time-scales (changes in context that progress in accordance with the weekly calendar and family influence processes). Copyright © Taylor & Francis Group, LLC.